MENINGKATKAN KEMAMPUAN MENGINGAT MELALUI PEMBERIAN LAYANAN PENGUASAAN KONTEN TEKNIK LOCIPADA SISWA KELAS X SMA NEGERI 6 MEDAN T.A 2014/2015 - Imam Syuhada Akbar; Milfayeti Milfayeti (Faculty of Psychology, Universitas Medan Area, 2015)
The purpose of this study is to examine the effectiveness of the technique loci in improving memory in class X SMAN 6 Academic Year 2014/2015. The method used is action research counseling (PTBK). The population of this study were students of class X-3 SMA Negeri 6 Medan which numbered 40 people. Data analysis techniques in this study using descriptive qualitative data analysis techniques. Based on the results obtained before the service is 26% and is still in the category of